High Variability of Fabry Disease Manifestations in an Extended Italian Family. (22nd April 2015) - Cammarata, Giuseppe; Fatuzzo, Pasquale; Rodolico, Margherita Stefania; Colomba, Paolo; Sicurella, Luigi; Iemolo, Francesco; Zizzo, Carmela; Alessandro, Riccardo; Bartolotta, Caterina; Duro, Giovanni; Monte, Ines
Abstract : Fabry disease (FD) is an inherited metabolic disorder caused by partial or full inactivation of the lysosomal hydrolase α -galactosidase A ( α -GAL). The impairment of α -GAL results in the accumulation of undegraded glycosphingolipids in lysosomes and subsequent cell and microvascular dysfunctions. This study reports the clinical, biochemical, and molecular characterization of 15 members of the same family. Eight members showed the exonic mutation M51I in the GLA gene, a disease-causing mutation associated with the atypical phenotype. The clinical history of this family highlights a wide phenotypic variability, in terms of involved organs and severity. The phenotypic variability of two male patients is not related to differences in α -GAL enzymatic activity: though both have no enzymatic activity, the youngest shows severe symptoms, while the eldest is asymptomatic. It is noticeable that for two female patients with the M51I mutation the initial clinical diagnosis was different from FD. One of them was diagnosed with Familial Mediterranean Fever, the other with Multiple Sclerosis. Overall, this study confirms that the extreme variability of the clinical manifestations of FD is not entirely attributable to different mutations in the GLA gene and emphasizes the need to consider other factors or mechanisms involved in the pathogenesis of Fabry Disease.